Macroscopic model for steel fiber reinforced high performance concrete based on unit cell calculations. Issue 1 (14th December 2021) - Pise, Mangesh; Brands, Dominik; Schröder, Jörg; Gebuhr, Gregor; Anders, Steffen
Abstract: The influence of reinforced steel fiber on the failure behavior of high performance concrete (HPC) is mainly characterized by the complex fiber‐matrix interaction at microscale. A phenomenological material model is developed for more efficient simulation of the overall material behavior of fiber reinforced HPC. For the calibration of the material parameters and to verify the efficiency of the presented phenomenological material model the simulation results of a virtual experiment using an ellipsoidal RVE and a macroscopic boundary value problem (BVP) are compared.